PERATURAN PERDAGANGAN INTERNASIONAL DI ASEAN DAN RRT: TANTANGAN DAN PELUANG BAGI UMKM - Anindya Belva Carissa; Rizal Fahmi; Nadira Hayfa Rizka (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study discusses the challenges and opportunities faced by Indonesian Micro, Small and Medium Enterprises (MSMEs) in facing international trade in the ASEAN region and the People's Republic of China (PRC). Amidst growing regulatory complexity, MSMEs are faced with barriers such as differences in technical standards, complicated customs procedures, and limited access to market information. However, there are also opportunities from free trade agreements and regional initiatives that can be utilized to expand markets. Through a qualitative approach and literature review, this research identifies key barriers for MSMEs, including limited management capacity, and the importance of collaboration between the government and private sector in developing comprehensive solutions to improve MSME competitiveness in the global market.